PENGUATAN IKM MANDIRI BERBASIS PERENCANAAN PEMBELAJARAN DAN P5 DI SMP TAMAN DEWASA KUMENDAMAN YOGYAKARTA - Sukiyanto; Ani Widyawati; Murniningsih; Laily Rochmawati Listiyani (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
The aim of this program is to increase teachers' understanding of the teaching tools that have been provided by the Ministry of Education, Culture and Research and Technology for IKM Mandiri Berubah and assist teachers in linking the material with the Pancasila profile and P5 planning. The method for implementing this service uses the workshop method in stages. Implementation stages or steps are adjusted to the solution stages for priority problems or issues faced by partners. Each stage is accompanied by outcomes whose success can be measured. The results of this program are: (1) there has been a review of the results of the pre-questionnaire regarding IKM and P5, (2) a refresher has been carried out for teachers regarding IKM Mandiri Belajar, IKM Mandiri Berubah, and IKM Mandiri Sharing, especially the main differences between the three IKM Mandiri , (3) knowledge transfer has been carried out regarding the contents of the IKM Mandiri Changing learning tools for mathematics learning, (4) Facilitating the development of diversity materials and local wisdom related to mathematics learning, and the results of post-questionnaire results related to SMEs. Based on measurements, of the 39 respondents, 69.2% understood, 17.9% understood very well, and 12.8% did not understand the understanding of the implementation of the independent curriculum.